Die Gottessöhne und das menschliche Maß: Gen 6,1-4 - Seebass, Horst (Biblische Notizen, 2007)
This essay tries to show that Gen 6,1-4 is not a tradition of God’s punishment on the humanity and not the ending of eternal life of humanity as in Gen 3,22-24, but a tradition of a borderline for the sons of God not to mix with humanity and the introduction into a normal human lifetime granting 120 years as a gift transcending what Ps 90 saw as normal (70-80 years).